A method for preparing a non-precious metal supported carbon catalyst and its application in the hydrogenation of furfural to prepare furfuryl alcohol

Through two -step thermal solution to prepare non -precious metal load carbon catalysts, the problem of high temperature and high pressure in the existing technologies requires high temperature and high pressure, and realizes the transformation of branalthalene to brachyol under mild conditions, reducing production costs and increasing environmental protection. sex.

CN117181225BActive Publication Date: 2025-01-28XIANGTAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311144936.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-01-28
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

In the prior art, the catalyst for preparing furfurfural hydrogenation is expensive, and the reaction requires high temperature and high pressure, resulting in high production costs.

Method used

Two -step thermal solution is used to prepare non -precious metal loaded carbon catalysts, to form a complex through semi -polymer glucose impregnated metal organic skeleton, reduce the destruction of MOF structure during thermal solution, and obtain a catalyst with abundant pore structure and a good metal activity component.

Benefits of technology

Under mild conditions, the catalyst shows excellent catalytic activity. It can still maintain good hydrogenation performance after more than 10 cycles, reduce production costs, and improve the environmental protection of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117181225B_ABST
    Figure CN117181225B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a non-precious metal-supported carbon catalyst and its application in the preparation of furfuryl alcohol by hydrogenation of furfural. A semi-polymerized glucose solution is fully impregnated with a metal organic framework under reduced pressure to obtain a composite, the excess semi-polymerized glucose on the surface is washed to remove the semi-polymerized glucose and fully dried, the composite structure is stabilized by low-temperature pyrolysis, and the catalyst is obtained by secondary high-temperature pyrolysis. Compared with traditional activated carbon-supported non-precious metal and metal organic framework-derived carbon catalysts, the catalyst of the present invention has a suitable mesopore size and a uniform distribution of active metals, and shows excellent catalytic activity in the reaction of selective hydrogenation of furfural to prepare furfuryl alcohol. The catalyst of the present invention uses semi-polymerized glucose to disperse the active metal center, increases the content of the carrier carbon, and increases the activity, selectivity and stability of the catalyst. There is no problem of secondary pollution of metal ions caused by the loss of active metals during recycling, and the entire reaction process is easy to operate and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new chemical materials, and specifically relates to a preparation method of a non-precious metal supported carbon catalyst and application of the catalyst in preparing furfuryl alcohol by hydrogenating furfural. Background Art

[0002] Biomass energy uses organic matter from plants, animals and other biological sources as an energy source. Compared with traditional fossil energy, biomass energy is not only a renewable energy source, but its use can also help reduce greenhouse gas and pollutant emissions. Furfural (FFA) is a biomass platform molecule produced from lignocellulose. It is an important precursor for a variety of chemicals. Through catalytic hydrogenation, it can produce high value-added compounds such as furfuryl alcohol (FAL), 2-methylfuran (2-MF), tetrahydrofuran (THFAL), levulinic acid (LA), etc.

[0003] Furfural (FFA) is used to produce furfuryl alcohol (FAL). In order to ensure a good reaction effect, the catalyst usually needs to use metals such as copper, chromium, and palladium. The catalyst is expensive, and the reaction requires high temperature and high pressure, high equipment requirements, and high production costs. For example, Chinese invention CN201510662455.4 discloses a catalyst for preparing furfuryl alcohol by liquid phase hydrogenation of furfural and a preparation method thereof and a method for preparing furfuryl alcohol by liquid phase hydrogenation of furfural. The catalyst contains copper oxide, chromium oxide, calcium carbonate, and silicon dioxide. The molar ratio of copper oxide to chromium oxide is 1.8 to 2.4:1, the molar ratio of copper oxide to calcium carbonate is 1 to 8:1, and the molar ratio of copper oxide to silicon dioxide is 2 to 6:1. The catalyst has high activity and selectivity, but the catalyst needs to use a large amount of copper oxide and chromium oxide. The furfural reaction requires high temperature and high pressure conditions of 180 to 200°C and 5 to 8MPa, and the production cost is high.

[0004] Chinese invention CN 111116526 A provides a method for preparing furfuryl alcohol by hydrogenation of bio-based furfural catalyzed by MOF-based catalysts. Although the method of hydrogen transfer can obtain higher selectivity and yield of furfuryl alcohol, it needs to simultaneously meet the reaction conditions of high temperature (above 140°C), high pressure (above 2MPa) and long reaction time (more than 8 hours). All embodiments presented need to meet such conditions. Long-term operation under high temperature and high pressure will lead to very high energy consumption, resulting in high production costs and poor economic benefits.

[0005] It is reported that about 62% of FFA is used to produce FAL, and its commercial catalyst is CuCr 2 O 4 , however CuCr 2 O 4Toxic Cr is easily leached out under high temperature and high pressure reactions, and the catalyst cannot be reused. Therefore, it is very necessary to develop a highly active, reusable and environmentally friendly catalyst. Summary of the invention

[0006] In view of the technical problems that the catalysts in the above-mentioned furfural hydrogenation to prepare furfural alcohol are expensive, the reaction requires high temperature and high pressure, and the production cost is high, the present invention provides a method for preparing a non-precious metal-loaded carbon catalyst and its application in the furfural hydrogenation to prepare furfural alcohol. The non-precious metal-loaded carbon catalyst is prepared by two-step pyrolysis, and the catalyst precursor is a complex formed by semi-polymerized glucose impregnating a metal organic framework. Methanol is used as a solvent in the preparation process of the metal organic framework, and no acid or alkali solution is involved. A secondary carbon source is introduced into the metal organic framework material through a reduced pressure operation, which reduces the destruction of the MOF structure during the pyrolysis process. The resulting catalyst has a rich pore structure and the metal active components are well dispersed. The obtained non-precious metal-loaded carbon catalyst is used for the preparation of furfural by hydrogenation, and can show excellent catalytic activity under mild conditions. In the subsequent recycling experiment, the catalyst can still maintain excellent hydrogenation performance after more than 10 cycles.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a non-precious metal supported carbon catalyst comprises the following steps:

[0009] (1) Synthesis of a metal organic framework, wherein a metal salt and an organic ligand are respectively dissolved in methanol to obtain a metal salt solution and an organic ligand solution, and then the metal salt solution is uniformly dropped into the organic ligand solution, wherein the molar ratio of the metal salt to the organic ligand is 1:(2-10), and the mixture is kept warm in a water bath, centrifuged, washed and dried to obtain a metal organic framework material;

[0010] (2) Preparation of a semi-polymerized glucose solution: dissolving glucose in deionized water, and placing the resulting solution in a hydrothermal reactor for hydrothermal heating to obtain a semi-polymerized glucose solution;

[0011] (3) during the reduced pressure impregnation process, the semi-polymerized glucose solution obtained in step (2) is placed in a constant pressure funnel, and the metal organic framework material obtained in step (1) is placed in a flask with a branch tube, a closed system is formed at room temperature and a low pressure environment is generated, and the valve of the constant pressure funnel is slowly opened to allow the semi-polymerized glucose solution to drip into the flask with a branch tube drop by drop, and the composite is fully impregnated;

[0012] (4) A two-step pyrolysis process, wherein the composite obtained in step (3) is placed in a tubular furnace for the first step of pyrolysis, and nitrogen is introduced as a protective gas during the pyrolysis process. After cooling, the composite is placed in the tubular furnace again for the second step of pyrolysis to obtain a non-precious metal supported carbon catalyst.

[0013] Furthermore, in step (1), the metal salt is one or two of cobalt nitrate, cobalt acetate, cobalt chloride, ferric nitrate, ferric chloride, nickel nitrate, nickel acetate, nickel chloride, manganese nitrate, manganese chloride, and manganese acetate; and the organic ligand is one or more of 2-methylimidazole, 2-nitroimidazole, and imidazole-2-carboxaldehyde.

[0014] Furthermore, in step (2), the mass volume ratio of glucose to deionized water is 2-8 g:30-80 mL, the hydrothermal temperature is 120-160° C., and the hydrothermal time is 6-12 h.

[0015] Furthermore, in step (4), the temperature of the first pyrolysis step is 250-450°C, the heating rate is 1-4°C / min, the pyrolysis time is 60-360min, and the flow rate of nitrogen is 20-80ml / min.

[0016] Furthermore, in step (4), the temperature of the second step pyrolysis is 550-950°C, the heating rate is 1-4°C / min, the pyrolysis time is 60-360min, and the flow rate of nitrogen is 20-80ml / min.

[0017] The non-precious metal-supported carbon catalyst obtained by the above preparation method is used in the catalytic hydrogenation of furfural to prepare furfuryl alcohol.

[0018] Furthermore, the specific application is to mix the obtained non-precious metal supported carbon catalyst with furfural in a solvent, introduce a hydrogen source, and react in a high-pressure reactor to obtain furfuryl alcohol.

[0019] Furthermore, the mass ratio of the non-precious metal supported carbon catalyst to furfural is 1:(5-20), the solvent is selected from at least one of methanol, ethanol, propanol, isopropanol and water; and the hydrogen source is selected from high-purity hydrogen.

[0020] Furthermore, the mass volume ratio of furfural to solvent is (0.1-0.6) g: (10-30) mL; the hydrogen pressure is 0.5-1.5 MPa, the reaction temperature is 80-130° C., and the reaction time is 0.5-4 h.

[0021] The present invention uses semi-polymerized glucose as a secondary carbon source and allows it to enter the interior of a metal organic framework material or be coated on the outer surface through a reduced pressure impregnation method. The pyrolysis process greatly enhances the stability of the metal organic framework-derived material and can still maintain good catalytic activity during subsequent repeated experiments.

[0022] The beneficial effects of the present invention are:

[0023] 1. The non-precious metal supported carbon catalyst obtained by the present invention has a high specific surface area, developed pores, and good stability. At the same time, its raw materials are easily available, the synthesis method is simple, and it is easy to repeat, and it is expected to be mass-produced.

[0024] 2. The present invention uses methanol as solvent and does not require any environmentally unfriendly post-treatment processes such as strong acid or strong alkali; it does not involve the use of activators such as KOH and NaOH, which can improve the environmental friendliness of the process and will not hinder the effective expansion of the pore size.

[0025] 3. The semi-polymerization treatment of glucose combined with reduced pressure impregnation stabilizes the internal structure of the precursor metal organic framework material during pyrolysis, and the pore structure does not collapse on a large scale, thus avoiding obvious damage to the internal structure of MOF by direct pyrolysis. The metal active components have good dispersion, and the pore size distribution range of the porous carbon material is increased during the pyrolysis process, resulting in the appearance of a large number of mesopores, which is significantly beneficial to the adsorption and diffusion of reactants during catalytic hydrogenation reduction reactions.

[0026] 4. The non-precious metal-loaded carbon catalyst prepared by the present invention has the advantages of being green and environmentally friendly, having a high catalytic conversion rate and stable performance. It exhibits excellent catalytic activity in a wide range of applications for the selective hydrogenation of furfural to prepare furfuryl alcohol. The reaction can achieve complete conversion of furfural at a hydrogen pressure of 1.0-1.5 MPa and a temperature range of 100-130°C. The yield of furfuryl alcohol is stabilized at more than 91%, and the yield of furfuryl alcohol can be as high as 96.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of a specific process for preparing a supported carbon catalyst using metal cobalt as an example in Example 1;

[0028] Figure 2 This is a standard gas chromatogram of reactants and products involved in the preparation of furfuryl alcohol by hydrogenation of furfural;

[0029] Figure 3 This is a scanning electron microscope image of the catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The present invention is described in detail below with reference to the embodiments, but the present invention is not limited thereto.

[0031] Example 1

[0032] Synthesis of metal organic framework: Weigh 39.36g of 2-methylimidazole and dissolve it in 120ml of anhydrous methanol, weigh 17.46g of cobalt nitrate hexahydrate and dissolve it in 30ml of anhydrous methanol, then place the beaker containing 2-methylimidazole solution in a 25°C water bath stirring pot, drip the cobalt nitrate hexahydrate solution into it at a uniform speed, start stirring, and the speed is 100r / min. After 36h of reaction, put it into a centrifuge tube and centrifuge it in a centrifuge. After centrifugation, wash it three times with methanol to obtain a purple metal organic framework material and dry it for use.

[0033] Preparation of semi-polymerized glucose: Weigh 6 g of glucose and 60 ml of deionized water into a polytetrafluoroethylene reactor liner respectively, and place them in the reactor for hydrothermal treatment after ultrasonic dissolution. The hydrothermal temperature is 140°C and the hydrothermal time is 10 h.

[0034] Reduced pressure impregnation process: Pour the semi-polymerized glucose solution into the constant pressure funnel and plug it, place the dried metal organic framework material and the magnetic stirrer in a flask with a branch tube, connect the lower end of the constant pressure funnel to the flask with a branch tube, and apply vaseline to the connection to maintain air tightness. Connect the other end of the flask with a branch tube to a vacuum pump, evacuate the inside of the flask with a branch tube, and then put the device into a water bath stirring pot (room temperature) with a stirring speed of 100r / min. Open the valve of the constant pressure funnel, drip the semi-polymerized glucose solution above into the flask with a branch tube below, and close the valve until the semi-polymerized glucose solution covers the purple metal organic framework material, and impregnate for 24h.

[0035] Two-step pyrolysis process: After the impregnation metal organic framework material is centrifuged, washed and dried, it is heated at 400℃ and N 2 The carbon material was pyrolyzed at 700 °C and N for 2 h (heating rate 4 °C / min) and then taken out after natural cooling. 2 The mixture was pyrolyzed under atmosphere for 2 h (heating rate 4 °C / min), and after cooling, a porous carbon catalyst supported by metal cobalt was obtained.

[0036] Take 0.03g of the above catalyst and place it in a 50mL polytetrafluoroethylene high-pressure reactor. Weigh 0.3g of furfural and add 15mL of isopropanol as a solvent to the reactor. Pass hydrogen back and forth several times to replace the air in the reactor. On this basis, the hydrogen pressure is increased to 1.2MPa, the magnetic stirring speed is 800rmp, and the reaction temperature is set to 120°C to evaluate the catalyst performance. The results show that the above catalyst exhibits excellent performance in the furfural hydrogenation catalytic process. After 3h of reaction, the furfural conversion rate reaches 100% and the furfuryl alcohol yield is 96.2%.

[0037] Example 2

[0038] The preparation process of the catalyst in Example 2 is the same as that in Example 1, except that the hydrogen pressure during the catalytic reaction is 1.3 MPa, the furfural conversion rate reaches 100% after 3 hours of reaction, and the furfuryl alcohol yield is 95.2%.

[0039] Example 3

[0040] The preparation process of the catalyst in Example 3 is the same as that in Example 1, except that the reaction temperature during the catalytic reaction is 130° C., the furfural conversion rate reaches 100% after 3 hours of reaction, and the furfuryl alcohol yield is 92.6%.

[0041] Comparative Example 1

[0042] The preparation of the catalyst in Comparative Example 1 does not involve the process of reduced pressure impregnation of semi-polymerized glucose to form a complex (i.e., direct pyrolysis to prepare MOF without carbon coating of semi-polymerized glucose), and the other steps are the same as those in Example 1. After 3 hours of reaction, the furfural conversion rate reaches 60.2%, and the furfuryl alcohol yield is 59.3%.

[0043] Comparative Example 2

[0044] In Comparative Example 2, the catalyst was heated at 700°C and N 2 The atmosphere was then pyrolyzed at high temperature for 2 h (heating rate 4°C / min) to obtain the product. The other steps were the same as in Example 1. After 3 h of reaction, the furfural conversion rate reached 82.8%, and the furfuryl alcohol yield was 80.3%.

[0045] By comparing the experimental data of the above embodiments and comparative examples, it can be seen that the present invention obtains a non-precious metal supported carbon catalyst with excellent performance by superimposing a semi-polymerized treatment of glucose with a reduced pressure impregnation and coordinating with a two-step pyrolysis. Compared with the catalyst without the reduced pressure impregnation treatment of semi-polymerized glucose (i.e., without carbon coating of semi-polymerized glucose) or without the two-step pyrolysis, the catalyst obtained by the present invention significantly improves the furfural conversion rate and the furfuryl alcohol yield.

Claims

1. An application of a non-precious metal supported carbon catalyst in the catalytic hydrogenation of furfural to prepare furfuryl alcohol, characterized in that: The preparation method of the non-precious metal supported carbon catalyst comprises the following steps: (1) Synthesis of metal organic framework materials: dissolving a metal salt and an organic ligand in an appropriate amount of methanol solution to obtain a metal salt solution and an organic ligand solution, respectively, wherein the metal salt is one or two of cobalt nitrate, cobalt acetate, cobalt chloride, ferric nitrate, ferric chloride, nickel nitrate, nickel acetate, nickel chloride, manganese nitrate, manganese chloride, and manganese acetate; and the organic ligand is one or more of 2-methylimidazole, 2-nitroimidazole, and imidazole-2-carboxaldehyde; then the metal salt solution is evenly dropped into the ligand solution, and the molar ratio of the metal salt to the ligand is controlled in the range of 1: (2-10), and the mixture is fully stirred in a constant temperature water bath, centrifuged, washed, and dried to obtain the metal organic framework material; (2) Preparation of semi-polymerized glucose solution: Glucose is dissolved in deionized water, and the resulting solution is placed in a reactor for hydrothermal reaction at a temperature of 120-140° C. to obtain a semi-polymerized glucose solution; (3) Reduced pressure impregnation process: the semi-polymerized glucose solution obtained in step (2) is placed in a constant pressure funnel, and the metal organic framework material obtained in step (1) is placed in a flask with a branch tube, a closed system is formed at room temperature and a low pressure environment is generated, and the valve of the constant pressure funnel is slowly opened to allow the semi-polymerized glucose solution to drip into the flask with a branch tube drop by drop, and the composite is fully impregnated; (4) Two-step pyrolysis process: The composite obtained in step (3) is placed in a tubular furnace for the first step of pyrolysis. Nitrogen is introduced as a protective gas during the pyrolysis process. After cooling, the composite is placed in the tubular furnace again for the second step of pyrolysis to obtain a non-precious metal supported carbon catalyst.

2. The use according to claim 1, characterized in that: In step (2), the mass volume ratio of glucose to deionized water is 2-8 g: 30-80 mL, and the hydrothermal reaction time is 6-12 h.

3. The use according to claim 1, characterized in that: The temperature of the first step pyrolysis is 250-450°C, the heating rate is 1-4°C / min, the pyrolysis time is 60-360 min, and the nitrogen flow rate is 20-80 mL / min.

4. The use according to claim 1, characterized in that: The temperature of the second step pyrolysis is 550~950℃, the heating rate is 1~4℃ / min, the pyrolysis time is 60~360 min, and the nitrogen flow rate is 20~80 mL / min.

5. The use according to claim 1, characterized in that: The non-precious metal supported carbon catalyst and furfural are mixed in a solvent, a hydrogen source is introduced, and the mixture is reacted in a high-pressure reactor to obtain furfural alcohol.

6. The use according to claim 5, characterized in that: The mass ratio of the non-precious metal supported carbon catalyst to furfural is 1:(5-20), the solvent is selected from at least one of methanol, ethanol, propanol, isopropanol and water; and the hydrogen source is selected from high-purity hydrogen.

7. The use according to claim 5, characterized in that: The mass volume ratio of furfural to solvent is (0.1~0.6) g: (10~30) mL; the hydrogen pressure is 0.5~1.5 MPa, the reaction temperature is 80~130°C, and the reaction time is 0.5~4h.

Citation Information

Patent Citations

  • A catalyst for the liquid-phase hydrogenation of furfural to furfuryl alcohol, its preparation method, and a method for the liquid-phase hydrogenation of furfural to furfuryl alcohol.

    CN106582671B

  • Method for preparing furfuryl alcohol by catalyzing bio-based furfural hydrogenation through MOF-based catalyst

    CN111116526A

  • Method for preparing furfuryl alcohol by catalyzing furfural with nitrogen-doped porous carbon-coated non-noble metal catalyst

    CN111085232A